2004
DOI: 10.1203/01.pdr.0000141982.38959.10
|View full text |Cite
|
Sign up to set email alerts
|

Blood Transfusion Increases Functional Capillary Density in the Skin of Anemic Preterm Infants

Abstract: Direct visualization of the microcirculation at the level of the skin capillaries may provide information on the quality of tissue perfusion. Orthogonal polarization spectral imaging (OPS) enables noninvasively direct observation of those blood vessels. OPS was applied to the upper arm of 13 preterm anemic infants [median (95% confidence interval) gestational age: 26 wk (25-26 wk); birth weight: 730 g (652-789 g)] before and 2 and 24 h after transfusion (Tx). OPS images of skin perfusion were continuously reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 15 publications
(13 reference statements)
2
38
0
2
Order By: Relevance
“…OPS data for functional vessel density, diameter of microvessels, and red blood cell velocity correlated well with data obtained by fluorescence microscopy [7,13]. Despite the use of OPS imaging in a variety of conditions and organs [8,11,12,16,24], and the attractiveness of direct visualization of microcirculation, the quantification of changes and their physiologic and clinical relevance remains controversial [1, 4, 8, 11, 12, 15-18, 23, 24]. The proposed criteria include visible capillaries, clearly visible flow of individual erythrocytes versus large thrombosed vessels coursing in a criss-cross fashion [11,12], vessel diameter, red blood cell velocity [10,19,20], and functional capillary density [8,15,16,24].…”
Section: Discussionsupporting
confidence: 73%
“…OPS data for functional vessel density, diameter of microvessels, and red blood cell velocity correlated well with data obtained by fluorescence microscopy [7,13]. Despite the use of OPS imaging in a variety of conditions and organs [8,11,12,16,24], and the attractiveness of direct visualization of microcirculation, the quantification of changes and their physiologic and clinical relevance remains controversial [1, 4, 8, 11, 12, 15-18, 23, 24]. The proposed criteria include visible capillaries, clearly visible flow of individual erythrocytes versus large thrombosed vessels coursing in a criss-cross fashion [11,12], vessel diameter, red blood cell velocity [10,19,20], and functional capillary density [8,15,16,24].…”
Section: Discussionsupporting
confidence: 73%
“…Diameters of the vessels measured in our study ranged from 7 to 24 m. In neonates, vessels larger than 25 to 30 m are deeper in the dermis and only small loops can be observed before the vessel disappears into the deeper layer (33,34). In neonates due to the small size of the vessel, arterioles, capillaries, and post capillary venules cannot be clearly distinguished (8,9).…”
Section: Discussionmentioning
confidence: 67%
“…The recent development of new technologies has helped to investigate these changes in adult patients with sepsis (5)(6)(7). Previous studies have shown that parameters of microcirculation such as microvessel diameter, red blood cell velocity, and functional small vessel density (FSVD) can be measured in the skin of term and preterm infants by Orthogonal Polarization Spectral (OPS) imaging in the first week of life (8) and that FSVD increases after elective blood transfusion in anemic neonates (9). The microcirculation of the skin plays an important role in maintaining a constant body temperature and in regulating the fluid balance (10,11).…”
mentioning
confidence: 99%
“…SDF images of 10 s were obtained on three different spots of the right inner upper arm (preductal arm). As we have shown previously, the upper region of the arm provides a good image quality and is easy to access (36)(37)(38).…”
Section: Microcirculation and Hypotensionmentioning
confidence: 72%